Analysis of The Effect Brand Equity on Consumer Purchase Decisions in Telkomsel Products - Hastuti, Hastuti; Rusdin, Rusdin (International Journal of Management Progress, 2023)
The purpose of this research is to identify and examine the effect of brand equity on consumer purchasing decisions for Telkomsel products. This study had 1,585 respondents, and the slovin formula was used to select the sample, resulting in a total of 94 responses. This study uses quantitative research for the type of data. The systematic study of parts, phenomena, and quality relationships is known as quantitative research. Questionnaires were used to collect data for this research. A questionnaire is a way of getting information from a large number of people, or respondents, by asking them a large number of questions. The information checking technique used in this study is direct relapse examination using the following formula, simple linear regression analysis is used to determine the effect of brand equity on consumer purchasing decisions of Telkomsel products: The relationship between one independent variable (X) and the dependent variable (Y). Information collection techniques using polling instruments. Simple linear regression is used in the analytic approach of this study. With a tcount (13.089) greater than ttable (1.661) and a significant probability value of 0.000 0.05, this study shows that brand equity has a positive effect. This shows that the purchase decision is significantly positively influenced by brand equity